СПОСОБИ ВІДТВОРЕННЯ ВІЗАНТІЙСЬКИХ СИМВОЛІВ У СВІТОВІЙ ПОЕЗІЇ ЕПОХИ МОДЕРНІЗМУ (зіставний аналіз словесних образів американської, канадської, російської та української поезії) - Бєлєхова, Лариса Іванівна (Studia Philologica, 2013)
This article suggests a comprehensive analysis of Modern poetic texts and  explains the peculiarities of Byzantian symbols. A special attention is drawn to reveling linguistic and stylistic means which ensure the embodiment of archetypal symbols into the texts of different poetic cultures.